Changes in the Forsaken Schooling and Migration Relationship in Tajikistan - Ilhom Abdulloev (Institute of Labor Economics (IZA), 2020)
We examine how the forsaken schooling phenomenon in migration evolved over time in Tajikistan. After completing compulsory schooling at ages 16-17, young men in Tajikistan are forsaking professional education because of opportunities to migrate for higher paid low-skilled jobs in the Russian Federation. We study how the forsaken schooling effect changed because of migrant-receiving Russia's recent tightened migration policy and economic slowdown, and policies promoting fair access to professional education in migrant-sending Tajikistan.
Keywords: O15; P46; F22; I24; 330; migration; traps; education; skill